2021
DOI: 10.1111/tbed.14127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Mycobacterium bovis in central parts of Malawi

Abstract: Bovine tuberculosis (bTB) is a neglected disease that affects cattle and humans. The burden of bTB is higher in developing countries as compared to industrialized countries. The reasons behind this discrepancy include the fact that bTB control measures, such as testing and slaughter of infected cattle and pasteurization of milk, are not usually practised in developing countries largely because of their high cost. To improve our understanding of bTB in developing countries, molecular typing studies are essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In Malawi, livestock are crucial to people's livelihoods, as they are in many other developing countries, such that the interaction between people and their livestock is unavoidable [ 3 ]. The spread of bTB to and within Malawi could be exacerbated by multiple factors such as; open local borders (allowing unregulated animal movement) between Malawi and neighbouring countries where bTB is documented as ‘enzootic’ [ [4] , [5] , [6] ], traditional livestock production systems characterised by communal grazing and mixing of animals from various localities.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Malawi, livestock are crucial to people's livelihoods, as they are in many other developing countries, such that the interaction between people and their livestock is unavoidable [ 3 ]. The spread of bTB to and within Malawi could be exacerbated by multiple factors such as; open local borders (allowing unregulated animal movement) between Malawi and neighbouring countries where bTB is documented as ‘enzootic’ [ [4] , [5] , [6] ], traditional livestock production systems characterised by communal grazing and mixing of animals from various localities.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent molecular epidemiological study, we revealed a high genetic diversity of M. bovis strains circulating in central Malawi [ 3 ] However, the general epidemiology and risk factors associated with bTB in cattle in Malawi are still required for a better understanding of the disease. Therefore, this study aimed to generate updated bTB epidemiological evidence in cattle and highlight the zoonotic TB threat to humans in Malawi.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations